Stories of courage in a group of adults with Substance Use Disorder. (December 2019) - Di Maggio, Ilaria; Santilli, Sara; Nota, Laura
Abstract: The treatment for drug addiction is considered a difficult path for the most of patients. As matter of fact, individuals with Substance Use Disorder (SUD) experience numerous challenges before, during and after the treatment (e.g. tackling an unpredictable, uncertain and paradoxically negative future, tackling the anxiety and anticipatory fear of physical pain associated with abstinence; decide to go beyond self-justification and self-deception). Courage could be considered a positive and functional resource to help people with SUD to face challenges and difficulties related to treatment. In connection therewith, the aim of this study was to examine, using an embedded mix method analysis, the personal stories of courage of 80 individuals with SUD in order to identify the themes and types of courage used in their life. The analysis carried out showed that individuals with SUD reported more frequently stories of courage related to their SUD condition respect to other life situation. Moreover, the quantitative analysis showed that participants used more frequently psychological courage respect to moral and physical courage when these stories were referred to their SUD condition then other life situations. Highlights: The analysis carried out showed that individuals with SUD reported more frequently stories of courage related to their SUD condition respect to other life situation. The analysis carried out showed that participants used more frequently psychological courage respect to moral and physical courage The analysis carried out showed that participants used more frequently psychological courage when these stories were referred to their SUD condition then other life situations